2014
DOI: 10.1093/cvr/cvu126
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of miRNA-mediated regulation of TGF  signalling during mouse cardiogenesis

Abstract: We show for the first time that TGFβ signalling is directly regulated by the miRNA mechanism during myocardial wall morphogenesis. Increased TGFβ activity plays a major role in the cardiac defects caused by myocardial deletion of Dicer1. Thus, miRNA-mediated regulation of TGFβ signalling is indispensable for normal cardiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…Endothelial cell (EC) injury and inflammation have been largely implicated in the formation of coronary atherosclerosis [5, 6]. It is also well-established that microRNAs (miRNAs) participate in pathological processes in the cardiovascular system, such as endothelial dysfunction, inflammation, apoptosis, angiogenesis, and atherosclerosis [7, 8]. Therefore, it is possible that miRNAs may have a potential relationship with EC injury and inflammation in CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell (EC) injury and inflammation have been largely implicated in the formation of coronary atherosclerosis [5, 6]. It is also well-established that microRNAs (miRNAs) participate in pathological processes in the cardiovascular system, such as endothelial dysfunction, inflammation, apoptosis, angiogenesis, and atherosclerosis [7, 8]. Therefore, it is possible that miRNAs may have a potential relationship with EC injury and inflammation in CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Mutant hearts showed an upregulation of a dozen contractile proteins such as actinin, cTnC, MHC[s3], myosin light chain [s4](MLC)1V and MLC2V, as well as an increase in transforming growth factor β receptor (TGFBR)1 activity. By contrast, blocking TGFBR1 activity partially rescues the heart from defects caused by the inactivation of Dicer in vivo [21]. Specifically, myocardial inactivation of Dicer under the control of a promoter for the cardiomyocyte structural protein alpha myosin heavy chain (αMHC) in mice resulted in dilated cardiomyopathy, heart failure and postnatal lethality, which was consistent with the disruption in expression of cardiac contractile proteins, as well as changes in sarcomeric structure [22].…”
Section: Mechanisms Of Mirnas In the Regulation Of Normal Cardiovascumentioning
confidence: 99%
“…Recently, Peng [s2] et al . demonstrated that specifically inactivating Dicer in the myocardium by crossing cTnt-Cre mice with Dicer loxP mice efficiently inactivated target genes in cardiomyocytes at mid-gestation, thus leading to severe myocardial wall defects, including reduced cell proliferation, increased cell death and spongy myocardial wall, and ultimately resulting in the death of all mutants between E14.5 and E16.5 [21]. Mutant hearts showed an upregulation of a dozen contractile proteins such as actinin, cTnC, MHC[s3], myosin light chain [s4](MLC)1V and MLC2V, as well as an increase in transforming growth factor β receptor (TGFBR)1 activity.…”
Section: Mechanisms Of Mirnas In the Regulation Of Normal Cardiovascumentioning
confidence: 99%
“…Available data have suggested that miRNAs target genes that regulate neurulation and cardiogenesis, including transcription factors and genes in growth factor signaling (e.g., the TGFβ and Wnt families) [36; 40; 48; 49]. …”
Section: Micrornas As Biomarkers For Detection Of Embryonic Malformatmentioning
confidence: 99%